Modular and self-contained microfluidic analytical platforms enabled by magnetorheological elastomer microactuators - Zhang, Yuxin (2021)
Portability and low-cost analytic ability are desirable for point-of-care (POC) diagnostics; however, current POC testing platforms often require time-consuming multiple microfabrication steps and rely on bulky and costly equipment. This hinders the capability of microfluidics to prove its power outside of laboratories and narrows the range of applications. This paper details a self-contained microfluidic device, which does not require any external connection or tubing to deliver insert-and-use image-based analysis. Without any microfabrication, magnetorheological elastomer (MRE) microactuators including pumps, mixers and valves are integrated into one modular microfluidic chip based on novel manipulation principles. By inserting the chip into the driving and controlling platform, the system demonstrates sample preparation and sequential pumping processes. Furthermore, due to the straightforward fabrication process, chips can be rapidly reconfigured at a low cost, which validates the robustness and versatility of an MRE-enabled microfluidic platform as an option for developing an integrated lab-on-a-chip system.